The Enduring Legacy : Oil, Culture, and Society in Venezuela - Tinker Salas, Miguel (Book collections on Project MUSE., 2009)
Assesses the role of a foreign-dominated oil industry in the construction of Venezuelan citizenship and the industry's impact on culture and politics, as well as race, class, and labor relations of the nation.